Utilization rate and length-weight relationship of shortfin scad (Decapterus macrosoma) in Bali Strait Indonesia - Bintoro Gatut (EDP Sciences, 2021)
Shortfin scad (Decapterus macrosoma) is an essential economic fish resource that spreads over tropical and subtropical oceans and is mostly caught in Bali Strait. High market demand for this fish leads to an increase in fishing efforts. In contrast, uncontrolled fishing efforts will threaten its sustainability and economic potential. This research was conducted based on catches during February – March 2020 for total samples of 1,115 fish and catch-effort time series secondary data (2008-2019). Length-weight data were analyzed using linear regression. The utilization level is predicted using the surplus production model analysis, Schaefer and Fox models, to estimate maximum sustainable yield (MSY). Results informed that based on Fox model analysis, values of sustainable catch (YMSY), optimum fishing effort (fopt), and total allowable catch (YTAC) were 1,585 tons/year, 1,782 trips/year, and 1,268 tons/year, respectively. The utilization rate value was 125%. An increase in fishing efforts led to the excess amount of catch over the MSY level. In addition, based on length-weight relationship analysis, the growth pattern of shortfin scad (D. macrosoma) was found negative allometric with equation W = 0.0175 L2.776. In conclusion, the fish has a fat body shape, and the stock is in overfishing condition.